Bioactives of coffee cherry pulp and its utilisation for production of Cascara beverage. (15th April 2017) - Heeger, Andrea; Kosińska-Cagnazzo, Agnieszka; Cantergiani, Ennio; Andlauer, Wilfried
Highlights: Coffee cherry pulp is rich in phenolic compounds. Cascara beverage from coffee cherry pulp may decrease waste from coffee production. Cascara beverage contains caffeine and phenolic compounds. Abstract: Coffee cherry pulp is a by-product obtained during coffee production. Coffee cherry pulp contains considerable amounts of phenolic compounds and caffeine. An attempt to produce Cascara, a refreshing beverage, has been made. Six dried coffee pulp samples and a beverage called Cascara produced in Switzerland out of one of those samples were investigated. Aqueous extraction of coffee pulps revealed a content of total polyphenols between 4.9 and 9.2 mg gallic acid equivalents (GAE)/g DM. The antioxidant capacity was between 51 and 92 μmol Trolox equivalents (TE)/g DM as measured by the assay with ABTS radical. Bourbon variety from Congo and maragogype variety showed highest caffeine contents with 6.5 and 6.8 mg/g DM. In all samples chlorogenic acid, protocatechuic acid, gallic acid and rutin were present. The beverage Cascara contained 226 mg/L of caffeine and 283 mg GAE/L of total polyphenols whereas antioxidant capacity amounted to 8.9 mmol TE/L.